Becoming abolitionists : police, protests, and the pursuit of freedom - Purnell, Derecka (Astra House, 2021)
"Purnell details how multi-racial social movements rooted in rebellion, risk-taking, and revolutionary love pushed her and a generation of activists toward abolition. The book travels across geography and time, and offers lessons that activists have learned from Ferguson to South Africa, from Reconstruction to contemporary protests against police shootings. Here, Purnell argues that police can not be reformed and invites readers to envision new systems that work to address the root causes of violence. Becoming Abolitionists shows that abolition is not solely about getting rid of police, but a commitment to create and support different answers to the problem of harm in society, and, most excitingly, an opportunity to reduce and eliminate harm in the first place"--